Frameworks Regulating Hunting for Meat in Tropical Countries Leave the Sector in the Limbo - van Vliet, Nathalie; Antunes, André Pinassi; Constantino, Pedro de Araujo Lima; Gómez, Juanita; Santos-Fita, Dídac; Sartoretto, Eugenio (Frontiers in Ecology and Evolution, 2019)
Despite restrictive legal frameworks, hunting for meat is a reality in tropical countries. In this policy paper, we argue that formal regulations are ill adapted to the contexts in which they should be applied and are characterized by gaps and contradictions that maintain the sector in a limbo. We use contemporary examples from Latin America and Africa described in detail in publications ranging from 2015 to 2018, to illustrate the need for legal reforms that clarify the rights to sell surplus of meat and align land tenure rights with wildlife use rights to suggest a new definition of subsistence hunting which accounts for the realities of communities from different cultural backgrounds.